Oxidation of Cellulose from Oil Palm Empty Fruit Bunch Using Hydrogen Peroxide in Alkaline Condition - Isroi, Isroi; Cifriadi, Adi (Center for Pulp and Paper, 2018)
There are growing interest to use cellulose as renewable material in order to replace non-renewable polymeric materials. Alteration and chemical modifications of the cellulose by oxidation is needed to improve its properties and functionality. The aim of this study was to evaluate oxidation effect of the cellulose from oil palm empty fruit bunch (OPEFB) using hydrogen peroxide in alkaline condition. Cellulose has been isolated and purified by sodium hydroxide method followed by sodium hypochlorite bleaching. The oxidation effect of the cellulose by hydrogen peroxide was investigated by component analysis of the lignocelluloses, visual analysis, physical and chemical properties. Fourier transform infrared spectroscopy was employed to evaluate the changes of functional groups. Digesting of the OPEFB by sodium hydroxide at temperature 160oC for 4 hours reduced lignin content from 22.58% to 16.60%, increase cellulose and hemicelluloses content from 60.76% to 73.87% and 25.86% to 30.95%, respectively. Treatment of the OPEFB pulp using sodium hypochlorite removed all residual lignin. Cellulose content was increased up to 90.86%. Degree of polymerization of the oxidized cellulose was reduced from 1997 to 658. Carboxyl groups of celluloses was significantly increased and confirmed by titration analysis. OPEFB cellulose fiber was damage and broken, meanwhile crystallinity of the cellulose was reduced.Keywords: cellulose, oxidation, oil palm empty fruit bunch, carboxyl group, crystallinity, physical propertiesÂ Oksidasi Selulosa dari Tandan Kosong Kelapa Sawit menggunakan Hidrogen Peroksida dalam Kondisi BasaAbstrakPerhatian untuk memanfaatkan selulosa sebagai polimer terbarukan untuk menggantikan polimer tidak terbarukan mengalami peningkatan. Perubahan dan modifikasi kimia selulosa melalui proses oksidasi diperlukan untuk meningkatkan sifat dan fungsi selulosa. Penelitian ini bertujuan untuk mempelajari pengaruh oksidasi selulosa dari tandan kosong kelapa sawit (TKKS) menggunakan hidrogen peroksida dalam suasana basa. Selulosa diisolasi dan dimurnikan dengan metode natrium hidroksida dan dilanjutkan dengan pemutihan natrium hipoklorit. Efek oksidasi selulosa oleh hidrogen peroksida dievaluasi menggunakan analisis komponen lignoselulosa, analisis visual, sifat fisik dan kimia. Analisis spektroskopi inframerah (FTIR) digunakan untuk mengevaluasi perubahan gugus fungsional selulosa. Pemasakan TKKS dengan natrium hidroksida pada suhu160oC selama 4 jam mengurangi kandungan lignin dari 22,58% menjadi 16,60%, meningkatkan kandungan selulosa dari 60,76% menjadi 73,87% dan hemiselulosa dari 25,86% menjadi 30,95%. Perlakuan pulp TKKS menggunakan natrium hipoklorit menghilangkan semua sisa lignin. Kandungan selulosa meningkat hingga 90,86%. Oksidasi selulosa dengan hidrogen peroksida menurunkan derajat polimerisasi selulosa dari 1997 menjadi 658. Gugus karboksil selulosa meningkat secara signifikan dan dikonfirmasi dengan analisis titrasi. Analisis visual menunjukkan kerusakan serabut selulosa, sesuai dengan pengurangan kristalinitas selulosa.Kata kunci: selulosa, oksidasi, tandan kosong kelapa sawit, gugus karboksil, kristalinitas, sifat fisikÂ